2011
DOI: 10.1186/gb-2011-12-4-220
|View full text |Cite
|
Sign up to set email alerts
|

The cullin protein family

Abstract: SummaryCullin proteins are molecular scaffolds that have crucial roles in the post-translational modification of cellular proteins involving ubiquitin. The mammalian cullin protein family comprises eight members (CUL1 to CUL7 and PARC), which are characterized by a cullin homology domain. CUL1 to CUL7 assemble multi-subunit Cullin-RING E3 ubiquitin ligase (CRL) complexes, the largest family of E3 ligases with more than 200 members. Although CUL7 and PARC are present only in chordates, other members of the cull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
403
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 420 publications
(411 citation statements)
references
References 95 publications
7
403
0
1
Order By: Relevance
“…We note that BRWD3 (24) is the Drosophila homolog of the human WDR9 gene (25) (also known as BRWD1), and the mutation of BRWD3 in Drosophila is known as ramshackle (21). Several members of this family of proteins are known to function as substrate receptors for CRL4 E3 ligases (20,26). We first established that BRWD3 interacted with dCRY in yeast two hybrid in a light-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that BRWD3 (24) is the Drosophila homolog of the human WDR9 gene (25) (also known as BRWD1), and the mutation of BRWD3 in Drosophila is known as ramshackle (21). Several members of this family of proteins are known to function as substrate receptors for CRL4 E3 ligases (20,26). We first established that BRWD3 interacted with dCRY in yeast two hybrid in a light-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Lightdependent binding of dCRY to BRWD3, along with the inhibition of light-dependent degradation of dCRY after BRWD3 knockdown, suggested that BRWD3 might function as a substrate receptor for a CRL4 E3 ligase in a manner similar to JET functioning as a substrate receptor for CRL1 E3 ligase (14). In CRL4 E3 ligases, DDB1 functions as a linker between the Cullin 4 scaffold and a WD40-protein substrate receptor (20,26). Indeed, when BRWD3 was expressed in human HEK293T cells and immunopurified, DDB1, CUL4A, CUL4B, and ROC1 copurified with it, indicating that BRWD3 is a substrate receptor for a CRL4 E3 ligase (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…npg nucleus to target transcription factors and nucleotide excision repair proteins (reviewed in [6][7][8]). Moreover, in response to environmental toxins, the extreme N terminus of CUL4B binds to the aryl hydrocarbon receptor (AhR) to form a distinct E3 ligase that catalyzes the ubiquitination and degradation of the estrogen receptor, progesterone receptor, and AhR itself [15].…”
Section: Discussionmentioning
confidence: 99%
“…CUL4B is a member of the cullin-RING ubiquitin ligase (CRL) family, which is the largest E3 ligase subtype in mammals that controls a wide spectrum of cellular processes including cell cycle, DNA replication and repair, signaling, transcription, and embryonic development (reviewed in [6][7][8]). CRLs are multimeric E3 ligase complexes that assemble on the elongated cullin scaffold: the RING domain adaptor Rbx1/Roc1 recruits the E2 ubiquitin-conjugating enzyme and interacts with the C-terminal cullin homology domain, while the cullin N-terminus associates with a cullin-specific adaptor protein to recruit a large family of substrate receptors, each of which can bind multiple substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most extensively studied systems that produce K48-linked Ub chains is the SCF (Skp1-Cullin1-F-box) E3-directed ubiquitination. SCF is a member of the multisubunit Cullin-RING E3 Ub ligase (CRL) family, the largest of all E3s (2). CRL contains a tandem of a large scaffold protein [Cullin (CUL)] and a RING domain-containing protein (ROC1/Rbx1) that typically associates with an adaptor protein (such as Skp1) in complex with a substrate recognition protein (such as F-box protein).…”
mentioning
confidence: 99%